Temperatures of Vein Formation Associated With Plate Interface Deformation Constrained by Oxygen and Clumped Isotope Thermometry - T.‐W. Chen; A. Smye; M. Lloyd; D. Fisher; Y. Hashimoto (Geochemistry, Geophysics, Geosystems, 2024)
Abstract Tectonic mélanges, characterized by conditions reflective of modern subduction fault zones, preserve mineral veins formed through mass transfer, a mechanism influencing the slip behavior of subduction megathrusts. In this study, we apply secondary ion mass spectrometry quartz‐calcite oxygen isotope thermometry and clumped isotope thermometry to examine the temperatures of vein formations in six mélange units in the Cretaceous Shimanto belt and one mélange in the Kodiak accretionary prism. Calcite in the veins exhibits δ13CPDB values ranging from −17.2‰ to −6.8‰, indicative of a carbon source mixing with sedimentary carbonate and organic matter. δ18OSMOW values of calcite range from +11.1‰ to +17.2‰; quartz yields δ18OSMOW values of +14.9‰ to +21.7‰. Oxygen isotopic signatures in minerals reveal that most vein‐forming fluids are significantly affected by rock buffering, while some retain isotopic compositions of seawater and meteoric water. Temperature estimates, derived from both thermometers, fall within the range of 100–250°C. Notably, vein temperatures remain constant across diverse vein types and mélange units with distinct maximum temperatures. The combined temperature records and fluid isotopic compositions imply vein formations at shallower depths linked to the incorporation of seawater, meteoric water, and fluid released from early dehydration reactions. At greater depths, vein formations are associated with fluid released from clay dehydration and long‐distance fluid flow. Reduced vein formations between 250 and 350°C may correlate with a shift to fluid‐unsaturated conditions resulting from clay hydration reactions. Our study highlights potential mechanical and hydraulic variations within the thermal conditions of 100–350°C along the plate boundary driven by fluid‐mineral interactions.